The school library and information needs surrounding topics of adolescent sexuality - Muñoz Alvarado, María Daniela (2013)
This paper refers to the issue of the role of the school library to adolescents and to the new Education Curriculum for Comprehensive Sexuality Affectivity and the Ministry of Education. Today, young people are exposed to a lot of changes, both internally and externally, which reflects the imminently need of having reliable and quality information to support the decision-making. Therefore, the objective of this work is to establish the relationship between the informational needs of adolescents on the issue of sexual and reproductive health and the school library as an information source to meet those needs. Thus, the proposal of this paper consist in an active role by the school library not only as an information generator but also as support for the Study of Education Programs for Integral Sexuality and Affectivity and adolescents, this with new services and products specializing in the topic of sexuality.